2020
DOI: 10.1007/s12649-020-01074-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Fish Pond Sediments Composts as Organic Fertilizers

Abstract: Increased fish pond production is associated with the generation of various waste including fish pond sediments. Fish pond sediments could be a valuable source of nutrients for growing plants, however they require further processing in order to be applied to soil. Composting is considered one of the methods for processing fish pond sediments. The aim of this work was to investigate the potential of organic fish pond sediments to be managed through laboratory composting with selected waste materials and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…Sediments within each zone of the reservoir should be analysed for both physical and chemical composition prior to usage, in order to insure that the material is not contaminated with potentially toxic compounds (Dróżdż et al, 2020a). Literature items characteristically report that, if bottom sediment extracted from a water reservoir does not pose a threat to the environment, it is reasonable to use it (Tarnawski et al, 2017).…”
Section: Methods Of Bottom Sediment Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediments within each zone of the reservoir should be analysed for both physical and chemical composition prior to usage, in order to insure that the material is not contaminated with potentially toxic compounds (Dróżdż et al, 2020a). Literature items characteristically report that, if bottom sediment extracted from a water reservoir does not pose a threat to the environment, it is reasonable to use it (Tarnawski et al, 2017).…”
Section: Methods Of Bottom Sediment Managementmentioning
confidence: 99%
“…There are many examples in the literature of using bottom sediments from fish ponds. These sediments are subjected to biological processes and then used as fertilisers in the cultivation of, for example, Lilium perenne, Lolium multiflorum and feed grasses (Dróżdż et al, 2020a;Dróżdż et al, 2020b;Haque et al, 2016).…”
Section: Methods Of Bottom Sediment Managementmentioning
confidence: 99%
“…Therefore, periodic clearing of the aquaculture ponds is needed in order to avoid these issues. Depending on the type of aquaculture, cleaning of pond sediments can take place several times a year as is the case in organic aquaculture or once every several years, as is the case of aquaculture practiced in natural water bodies [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated the usefulness of sediment application in agriculture [ 9 , 10 , 11 ]. For example, sediment from pangasius ( Pangasianodon hypophthalmus ) mixed with organic amendments from rice straw could be a good fertilizer for cucumbers ( Cucumis sativus L.) [ 11 ], while fish sediments from organic aquaculture have been shown to be beneficial for white beans [ 2 ]. However, when considering the use of sediment in agriculture, physico-chemical analyses must be performed due to the fact that their composition varies depending on the type of aquaculture, the cultivated fish species and its age, the feed used, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Bottom sediments can be utilized in farming as a soil substitute (Ockenden et al, 2014) or a natural fertilizer rich in nutrients necessary for plant growth (Dr ożdż et al, 2020). This nutrient density is because of the accumulation of organic and mineral substances in the sediments, for example, the decomposition of aquatic organisms (Tan et al, 2019) or the by-products of their metabolic processes (El-Radaideh et al, 2014).…”
mentioning
confidence: 99%